Is the Get-passive Really that Adversative? - Coto Villalibre, Eduardo (Miscelánea: A Journal of English and American Studies, 2015)
The characteristics commonly attributed to central get-passives in the relevant literature include the possibility of taking an overtly expressed agent by-phrase, a dynamic meaning conveyed by the lexical verb, an animate and human referent who is at the same time responsible for the action expressed in the clause, and an adversative semantic implication of the past participle. This paper focuses on one of the abovementioned features: the semantic implication of get-passives, that is, whether the event described in the clause is beneficial or favorable for the subject (get awarded, get elected, get promoted), adversative or unfavorable for the subject (get arrested, get killed, get shot), or semantically neutral (get printed, get sent, get written). Data collected from a corpus-based analysis of the spoken British English component and other spoken ESL components of the International Corpus of English (ICE) will be deployed to argue against those claims which define the get-passive as a predominantly negative or adversative construction in Present-Day English.